Study on The Production and Marketing of Pineapples Worldwide - Andreea-Roxana FIRATOIU (CHIURCIU); Irina-Adriana CHIURCIU; Liviu MARCUTA; Aurelia-Ioana CHEREJI; Elena SOARE; Valentina VOICU; Alina MARCUTA (Communications of International Proceedings, 2021)
One of the most beloved tropical fruits in the world, the pineapple, offers significant health benefits and is rich in vitamin C, B vitamins, fiber, and minerals. The research on the production and marketing of pineapple around the world, highlights the main trends in production, area cultivated, value and quantity imports and exports for the period 2015-2019. The statistical data presented in this study was retrieved from specialized sites such as: Food and Agriculture Organization of the United Nations (Faostat) and Statista. Worldwide, the total pineapple production is estimated at 28,179,348 tonnes in 2019, increasing in comparison with the precedent years. The biggest pineapple producer is Costa Rica 3,328,100 tonnes (2019), needing to mention that starting with 2016 Costa Rica, Brazil, and the Philippines, assure almost one-third of the production of pineapples, globally.
Keywords: Imports and Exports of Pineapples; Pineapples; Production of Pineapple; Worldwide Area.